The Impact of Prior Learning Assessment on Student Success and Completion: A Systematic Literature Review - Fawaz Al-Malood (JETL (Journal of Education, Teaching and Learning), 2023)
Prior Learning Assessment (PLA) has gained substantial traction within post-secondary institutions across the United States in recent years as a mechanism to enhance accessibility and affordability for adult learners. The increased interest in PLA affirms the notion that learning, and competency gained through experience, training, and certifications acquired outside of post-secondary institutions may meet learning outcomes and competencies established by colleges and universities. Extensive research has been conducted on PLA methods and practices; however, there is a distinct gap in systematic evidence regarding how PLA interventions affect student success and completion in post-secondary education. This study addresses this gap by systematically reviewing the impact of PLA on these outcomes using the PRISMA framework. The search yielded 44 studies from 2010 to 2018. A total of 10 studies meeting the inclusion criteria were selected for full-text review, bibliometric analysis, and chronological review. The findings show a positive impact of PLA, with students benefiting from higher graduation rates, shorter completion periods, and reduced tuition costs. Notably, Black, and Hispanic students experienced the most substantial positive effects. However, the limited number of studies in this area underscores the need for additional research to delve deeper into the factors that contribute to the success and growth of PLA's programs, specifically, the role of college counselors in advising adult students on PLA options needs further study.